Current developments to use linear MALDI‐TOF spectra for the identification and typing of bacteria and the characterization of other cells/organisms related to infectious diseases. Issue 9 (1st August 2016) - Karger, Axel
Abstract : Within the past few years identification of bacteria by MALDI‐TOF MS has become a standard technique in bacteriological laboratories for good reasons. MALDI‐TOF MS identification is rapid, robust, automatable, and the per‐sample costs are low. Yet, the spectra are very informative and the reliable identification of bacterial species is usually possible. Recently, new MS‐based approaches for the identification of bacteria are emerging that are based on the detailed analysis of the bacterial proteome by high‐resolution MS. These "proteotyping" approaches are highly discriminative and outperform MALDI‐TOF MS‐based identification in terms of specificity, but require a laborious proteomic workflow and far more expertise and sophisticated instrumentation than identification on basis of MALDI‐TOF MS spectra, which can be obtained with relative simple and uncostly linear MALDI‐TOF mass spectrometers. Thus MALDI‐TOF MS identification of bacteria remains an attractive option for routine diagnostics. Additionally, MALDI‐TOF MS identification protocols have been extended and improved in many respects making linear MALDI‐TOF MS a versatile tool that can be useful beyond the identification of a bacterial species, e.g. for the characterization of leucocytes and arthropod vectors of infectious diseases. This review focuses on such improvements and extensions of the typical MALDI‐TOF MS workflow in the field of infectious diseases.